Serotonin, impulsive behaviour, and brain-wide networks - Fonseca, Madalena S. (2020)
The central neuromodulator serotonin (5-HT) has been implicated in a wide range of brain processes and is a main target of psychiatric drugs. Yet, the principles underlying its function, as well as the functional circuitry underpinning its effects, remain poorly understood. In this monograph, we combine selective optogenetic activation of serotonin neurons, whole-brain functional magnetic resonance imaging (fMRI), and quantitative behaviour to study the serotonergic system and the brain-wide networks it modulates. We start by testing the hypothesis that 5-HT facilitates impulse control, more specifically, the ability of animals to wait for delayed rewards. We find that, indeed, selective activation of serotonin neurons in the dorsal raphe nucleus (DRN), the chief source of 5-HT to the forebrain, is sufficient to prolong waiting for delayed rewards. In a series of additional experiments,we show that this effect has behavioural specificity and is independent of aversive and appetitive effects, establishing a strong link between 5-HT and behavioural persistence.